2002
DOI: 10.1007/s005950200169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress in Laparoscopic Cholecystectomy

Abstract: These findings suggest that the antioxidant defense system is stimulated less with less oxidative stress, providing further evidence to support the opinion that LC is a safe technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 26 publications
4
53
1
3
Order By: Relevance
“…In addition to these benefits, they also suggested that LC has less effects on oxidative stress than OC during surgery. Zulfikaroglu et al (2002) showed that the antioxidant defense system is stimulated less with less oxidative stress, providing further evidence to support the opinion that LC is a safe technique.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to these benefits, they also suggested that LC has less effects on oxidative stress than OC during surgery. Zulfikaroglu et al (2002) showed that the antioxidant defense system is stimulated less with less oxidative stress, providing further evidence to support the opinion that LC is a safe technique.…”
Section: Discussionmentioning
confidence: 53%
“…34 In humans, studies comparing plasma markers of lipid peroxidation between laparoscopic and open cholecystectomy reported increased levels of markers in both groups with significantly increased levels in open surgery. 7,30,35 Pneumoperitoneum performed in rats with a pressure of 5, 10 or 15 mmHg resulted in an incremental increase in the formation of free oxygen radicals in lung and liver tissues. 36 In the study by Nickkholgh and colleagues, 10 histological and biochemical evidence of liver reperfusion injury was demonstrable at 12 mmHg but not at 8 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Two trials were only described in short. 33,34 As no language restriction was used, four publications were translated. [35][36][37][38] Double publications of trial results by the same research group were considered one trial.…”
Section: Resultsmentioning
confidence: 99%